2020
DOI: 10.1177/0022034520943867
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analyses Identify a Novel Risk Locus for Nonsyndromic Cleft Palate

Abstract: The 3 major subphenotypes observed in patients with nonsyndromic orofacial clefts (NSOFCs) are nonsyndromic cleft lip only (NSCLO), nonsyndromic cleft lip with palate (NSCLP), and nonsyndromic cleft palate only (NSCPO). However, the genetic architecture underlying NSCPO is largely unknown. Here we performed a 2-stage genome-wide association study (GWAS) on NSCPO and replication analyses of selected variants in other NSOFCs from the Chinese Han population. We identified a novel locus (15q24.3) and a known locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…CL/P and CP have been historically analyzed separately [9][10][11][12]. While genetic studies have identified nearly 40 genetic regions (or loci) as significantly associated with risk to CL/P, fewer, around 10 loci, have been identified for CP [2,[13][14][15]. The findings for CP have mostly been identified in the Han Chinese population [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CL/P and CP have been historically analyzed separately [9][10][11][12]. While genetic studies have identified nearly 40 genetic regions (or loci) as significantly associated with risk to CL/P, fewer, around 10 loci, have been identified for CP [2,[13][14][15]. The findings for CP have mostly been identified in the Han Chinese population [15].…”
Section: Introductionmentioning
confidence: 99%
“…While genetic studies have identified nearly 40 genetic regions (or loci) as significantly associated with risk to CL/P, fewer, around 10 loci, have been identified for CP [2,[13][14][15]. The findings for CP have mostly been identified in the Han Chinese population [15]. These genetic studies, ranging from candidate gene approaches to genome-wide studies along with analysis of animal models, have provided insights into the genetic etiology of nonsyndromic OFCs [16].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) using both casecontrol (Birnbaum et al, 2009;Mangold et al, 2010) and caseparent trio designs (Beaty et al, 2010(Beaty et al, , 2011(Beaty et al, , 2013Leslie et al, 2016a) have identified multiple genetic risk factors for OFCs. There have been multiple GWAS for CL/P (Birnbaum et al, 2009;Grant et al, 2009;Beaty et al, 2010;Mangold et al, 2010;Camargo et al, 2012;Sun et al, 2015;Wolf et al, 2015;Leslie et al, 2016a;Yu et al, 2017;Butali et al, 2019;Huang et al, 2019), two genome-wide meta-analysis of CL/P (Ludwig et al, 2012;Leslie et al, 2017), and four GWAS of CP (Beaty et al, 2011;Leslie et al, 2016b;Butali et al, 2019;He et al, 2020). These studies have revealed a complex genetic architecture controlling risk to OFCs.…”
Section: Introductionmentioning
confidence: 99%
“…More than 40 different genes or regions have yielded genomewide significant associations with risk to CL/P from multiple populations, while one gene (GRHL3) has been clearly identified as associated with risk to CP [largely limited to populations of European ancestry (Leslie et al, 2016b)]. A recent case-control study of Han Chinese CP cases and controls also identified the region on chromosome 15q24.3 as associated with risk of CP (He et al, 2020). Of these recognized risk genes achieving genome-wide significance, four regions (IRF6 on 1q32-41, the gene desert on 8q24, markers on 10q25.3 and on 17q22) can explain about a quarter of the estimated heritability in risk to CL/P based on twin and family studies (Beaty et al, 2016;Lupo et al, 2019), which has been estimated to be around 90% for both CL/P and CP based on twin registry data in European populations (Grosen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…CL/P and CP have been historically analyzed separately 912 . While genetic studies have identified nearly 40 genetic regions (or loci) as significantly associated with risk to CL/P, fewer, around 10 loci, have been identified for CP 2,1315 . The findings for CP have mostly been identified in the Han Chinese population 15 .…”
Section: Introductionmentioning
confidence: 99%